Gambaran Kepuasan Pasien di Ruang Rawat Inap Kelas III Badan Layanan Umum Daerah Rumah Sakit Konawe - Syahruddin Sumera; Lina Marlina; Endang Susilawati; Saasa; Mustafa (Lembaga Penelitian Dan Pengabdian Kepada Masyarakat (LPPM), Institut Teknologi Dan Kesehatan (ITK) Avicenna, 2022)
Background: Satisfaction is a person's feeling of pleasure that arises after comparing his impression of performance and expectations. Patient satisfaction is related to the quality of hospital services. Objective: This study aims to study the description of patient satisfaction in Class III Inpatient Room BLUD Konawe Hospital. Methods: Descriptive study using a survey approach to class III inpatients in the Surgical, Internal and Child Care Inpatient Rooms at the Konawe Hospital BLUD as many as 34 people selected by purposive sampling from July 22 to August 22, 2022 using a questionnaire sheet instrument related to satisfaction patient. Data analysis using univariate analysis. Results: Of the 34 respondents, satisfaction with nursing services on the reliability aspect was 76.5%, on the assurance aspect (service guarantee) 97.1%, on the tangible aspect (physical appearance) 91.2%, on the empathy aspect (concern ) 85.3%, and in the aspect of responsiveness (quick response) 82.4%. Conclusion: That most of the respondents stated that they were satisfied with the nursing services in the Class III Inpatient Room at the Konawe Hospital BLUD.